LYSOSOMAL ACID HYDROLASES AND HYPERREACTIVITY TO ENDOTOXIN IN MICE INFECTED WITH BCG - Saito, Kazuhisa (The Rockefeller University Press, 1965)
Experiments are reported dealing with the correlation between activities of lysosomal acid hydrolases and hyperreactivity to endotoxin induced by BCG infection. Acid hydrolases were determined quantitatively in peritoneal MP, liver homogenate, and plasma of normal and hyperreactive mice. Mice infected with BCG not only exhibited a hyperreactive state to lethal effect of endotoxin, but also responded to endotoxin by rapid increase of acid hydrolases, especially of β-glucuronidase, in the plasma; whereas control mice responded to endotoxin by almost no change in plasma acid hydrolases. The extent of increase of β-glucuronidase in plasma of hyperreactive mice was shown to correlate fairly well with the degree of hyperreactivity to the lethal effect of endotoxin. Desensitization of such animals with endotoxin was found to cause a decreased response of plasma β-glucuronidase parallel with decreased mortality. A large amount of PPD exerted the similar effect to that of endotoxin in hyperreactive mice. Furthermore, the effect of PPD was decreased by desensitization of such animals with endotoxin, a fact which suggests contamination of PPD with endotoxin.